Role of Propranolol in the Management of Periocular Infantile Hemangioma - Qayyum, Seema (Pakistan Journal of Ophthalmology, 2016)
Purpose: To find the efficacy of oral ?-blocker Propranolol in the management of periocular infantile hemangioma in the pediatric population. Study Design: Prospective interventional case series. Place and Duration of Study: Department of Pediatric Ophthalmology, The Children's Hospital and Institute of Child Health, Lahore (Dec. 14 – Dec. 15). Material and Methods: In this study we included 15 patients found to be suffering from vision – threatening hemangioma. Patients were evaluated as per protocol approved in our hospital adapted from international studies. All patients underwent a complete medical examination by a pediatrician, cardiologist, and a dermatologist. When needed an MRI was arranged. Oral Propranolol was initiated between one month to twelve months of age. Results: A total of fifteen patients were treated with oral propranolol. There was a dramatic improvement with complete resolution of the lesion in 66.6% of patients. In two patients (13.3%) there was more than 50% decrease in the size of the lesion, whereas there was cessation of growth in two patients (13.3%). None of the patients developed any significant complication. The duration of drug use ranged from two to ten months, mean being 5.2 months with a standard deviation of 1.8. Propranolol was weaned off by tapering the dose over a period of two weeks on discontinuation of the drug. Conclusions: Oral propranolol significantly reduces the size of vision threatening periocular hemangiomas with minimal or no side effects. Key words: Peri-ocular Hemangioma, Propranolol,, Beta Blockers